Youth Empowerment through the Preservation of Minangkabau Traditional Arts: A Case Study of the Tapian Janiah Lunto Community - Fadil Ramadhanil; Muhamad Juanda; Irta Sulastri; Hermawati Hermawati (UIN Siber Syekh Nurjati Cirebon, 2025)
This article discusses the process of community empowerment through the preservation of traditional Minangkabau arts and culture carried out by the Tapian Janiah Lunto Community in Nagari Lunto, Sawahlunto City. This research begins with the problem of the fading of local cultural values and the increasing social vulnerability among adolescents due to the strong current of globalization. The main objective of the research is to describe how the arts of randai, plate dance, and traditional music are utilized as strategic instruments to strengthen cultural identity, build social solidarity, and prevent juvenile delinquency. This research uses a descriptive qualitative approach with data collection techniques such as interviews, participatory observation, and documentation studies. Data analysis was conducted thematically using the Asset Based Community Development (ABCD) framework to highlight the utilization of local cultural, social, and human resource assets as a basis for empowerment. The results show that the Tapian Janiah Community is able to create a safe, inclusive, and productive social space for the younger generation. Artistic activities not only preserve culture but also increase adolescent self-confidence, strengthen social cohesion, and provide a positive alternative that is effective in preventing deviant behavior. These findings confirm that local culture-based empowerment is a transformative strategy that can be implemented sustainably and replicated in other communities with similar characteristics